Deciphering functional biomolecule potential of marine diatoms through complex network approach. (December 2021) - Marella, Thomas Kiran; Bansal, Hina; Bhattacharjya, Raya; Himanshu,; Parmar, Nitesh; Chaurasia, Ankur; Watanabe, Makoto M.; Bhatnagar, Amit; Tiwari, Archana
Graphical abstract: Highlights: Major active ingredients and bioactivities of diatoms were elucidated. First report on complex network approach to identify active ingredients. Pathway analysis was done for targeted proteins to elucidate bioactivity. Diatom metabolites identified involve in 212 biological pathways. Abstract: Marine diatoms are unique reservoirs of bioactive compounds having enormous applications in therapeutics. But high-throughput screening methods are needed to elucidate the interaction between numerous biomolecules and their targets, facilitating rapid screening for novel drug molecules. So, in the present study chemical constituents were extracted from five marine diatoms using un-targeted metabolite profiling and in-silico virtual screening bioinformatics was employed to predict their bioactivity and molecular targets. A total of 17 chemical constituents out of 51 showed interactions with 76 protein targets associated with 213 pathways. Ingredient-target-pathway network revealed oleic acid, linoleic acid and cholest-5-en-3-ol as major active constituents. Core subnetwork and protein association network showed involvement of these compounds in key metabolic pathways related to cell signaling, cell growth and metabolism of xenobiotics. Thus, the present study for the first time revealed the main active ingredients and their associated pathways from marine diatoms using complex network approach.